Improvement of vacuum sealing drainage in the treatment of tuberculosis wound with sinus tract and related nursing care (结核性窦道治疗中负压封闭引流置管方式的改良及护理) - ZHOU Yu (周宇); CHEN Xiaoshuang (陈晓双); BIAN Hengjie (卞恒杰); GAO Li (高利); WANG Rui (王睿) (中西医结合护理)
Objective To summarize the application value of modified vacuum sealing drainage in the treatment of tuberculosis wound with sinus tract and related nursing interventions. Methods The clinical data of 6 patients with tuberculosis wound with sinus tract were retrospectively analyzed. Results The improved catheterization was more effective in the drainage of the exudates in and around the sinus, and promoted the closure of the sinus. Conclusion By improving the way of vacuum sealing drainage and standardizing postoperative care, the clinical effect of vacuum sealing drainage in the treatment of tuberculosis wound with sinus tract could be strengthened. (目的 总结结核性窦道治疗中负压封闭引流(VSD)置管方式的改良及护理经验。方法 收集2018年10月—2020年2月南京市中西医结合医院收治的6例结核性窦道患者的临床资料, 回顾性分析了结核性窦道治疗中VSD置管方式的改良及护理经验。结果 改良后的VSD置管方式对窦道内及窦道周围渗出物的引流更为通畅, 进一步促进了窦道的闭合。结论 通过对结核性窦道VSD置管方式的改良, 配合术后护理, 可以明显改善VSD的临床效果。)